(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the traumatic experiences of students of psychological counseling and educational guidance departments, and the significance of the differences in traumatic experiences according to gender variables (males - females), and the academic stage (first - fourth), as the research community consisted of (882) males and females, and consisted of The research sample consisted of (400) male and female students, and the validity of the scale was verified by two methods: (apparent honesty (arbiters’ sincerity, and construction validity), and the stability of the scale was verified by two methods, namely (retest method, and alpha-Cronbach equation), and the results showed that there are significant differences Statistical significance between the mean scores of the sample and the hypothetical mean of the scale, and this difference is in favor of the average scores of the sample, meaning that the students of the psychological counseling and educational guidance departments do not have traumatic experiences to a good degree, and that all the calculated t values are not significant (for gender and stage) and the interaction between (gender and stage) that is, there is no Statistically significant differences between (male - female) and the school stage (first – fourth).